REGRESSION MODELS OF RHEOENCEPHALOGRAPHIC INDICES, DEPENDING ON THE ANTHROPO-SOMATOMETRIC PARAMETERS OF THE BODY IN PRACTICALLY HEALTHY WOMEN WITH ENDO-MESOMORPHIC SOMATOTYPE - Serebrennikova О.А.; Semenchenko, V.V.; Моskovko G.S.; Tsyhalko, D.V.; Shayuk, A.V.; Karliychuk, M.A. (World of Medicine and Biology, 2017)
The article describes and analyzes regression models of individual indicators of cerebral circulation in practically healthy women of the endo-mesomorphic somatotype, depending on the features of anthropo-somatotypological indicators. Constructed all 5 possible time indices of rheoencephalogram with determination coefficient (R2) from 0.593 to 0.904; of the 5 possible amplitude indices of the rheoencephalogram, 3 of R2 from 0.540 to 720 were constructed; of the 8 possible derivatives of the rheoencephalogram, 7 with R2 from 0.528 to 0.865 were constructed. Constructed models with R2 more than 0.5 most often include: for amplitude rheoencephalogram indicators - body diameters (29,4%), cephalometric indices and thickness of skin and fat folds (by 23,5%); for the time indices of the rheoencephalogram - the thickness of skin and fat folds (35.7%), cephalometric indices (21.4%), longitudinal, circumferential dimensions and diameters of the body (by 10.7%); for derivative indices of the rheoencephalogram - the thickness of skin and fat folds (29.3%), the circumferential size of the body and the width of distal epiphyses of long limb bones (by 17.1%) and body diameters (14.6%).